What's Wrong with Computational Notebooks? Pain Points, Needs, and Design Opportunities - Chattopadhyay, Souti; Prasad, Ishita; Henley, Austin Z.; Sarma, Anita; Barik, Titus (ACM CHI Conference on Human Factors in Computing Systems, 2020)
Computational notebooks—such as Azure, Databricks, and Jupyter—are a popular, interactive paradigm for data scientists to author code, analyze data, and interleave visualizations, all within a single document. Nevertheless, as data scientists incorporate more of their activities into notebooks, they encounter unexpected difficulties, or pain points, that impact their productivity and disrupt their workflow. Through a systematic, mixed-methods study using semi-structured interviews (n=20) and survey (n=156) with data scientists, we catalog nine pain points when working with notebooks. Our findings suggest that data scientists face numerous pain points throughout the entire workflow—from setting up notebooks to deploying to production—across many notebook environments. Our data scientists report essential notebook requirements, such as supporting data exploration and visualization. The results of our study inform and inspire the design of computational notebooks.
Honourable Mention Award